Evaluation of Anti-inflammatory Activity of Trichosanthes dioica Roxb. Seeds (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Inflammation a complex disease associated with various symptoms. These symptoms can be managed with non-steroidal and steroidal anti-inflammatory drugs, which on long term use lead to severe side effects. To overcome this problem, natural products are used as an alternative source of the discovery of new entities to be used as compounds anti-inflammatory compounds. Trichosanthes diocia (T. diocia) belongs to Cucurbitaceae family. T. dioica a dioecious perennial herbaceous vegetable is rich source of vitamin C and minerals. In addition to fruits, leaves and tender shoots have been used in the indigenous system of medicine. The objective of the present study was to evaluate the anti-inflammatory activity of methanolic extract of Trichosanthes dioica seeds for scientific validation of the folklore claim of the plant. The extract was evaluated at three different concentration of 100, 200 and 400 mg/kg, p.o. Significant dose dependent anti-inflammatory activity was observed which was comparable with that of the standard drug indomethacin at dose of 10 mg/kg.